Pengaruh Penambahan Bilge Keel Terhadap RAO (Response Amplitude Operator) Kapal Patroli Cepat - Baihaque, Muhd Ridho; Nusyirwan, Deny; Marga Raharja, Adyk (Sustainable, 2024)
Maritime transportation plays a vital role in mobility within archipelagic regions, and Fast Patrol Boat are an efficient choice to meet the needs of defence and maritime patrol in Indonesia. The innovation of adding bilge keels to the vessel is expected to enhance the performance of fast patrol vessels. This study aims to identify and evaluate the motions of Fast Patrol Boat to understand their performance under various sea conditions. Fast Patrol Boat operating at high speeds require a responsive pitch motion, making them well-suited for safeguarding Indonesia's archipelagic waters. The analysis results show that patrol Boat equipped with bilge keels perform better in terms of response and manoeuvrability, especially at high speeds, compared to vessels without bilge keels, although for other degrees of freedom such as heave and roll motions, there is no significant difference between the two types of vessels